EFEKTIVITAS PENGGUNAAN METODE PEMBELAJARAN COURSE REVIEW HORAY BERBANTUAN ALAT PERAGA TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS II SMP DR. SOETOMO SURABAYA MATERI KESEBANGUNAN DAN KEKONGRUENAN (Universitas Dr. Soetomo, 2015)
The purpose of this study was to determine the mistakes made and the difficulties experienced by students Autism class V SDN Inclusion Mojo III Surabaya. Besides, the purpose of this study also want to know the causes and solution . From the analysis of the data obtained the following conclusion: The percentage of errors made autistic student class V SDN Mojo III Surabaya in solving mathematical word problems on the subject of the Commission and the FPB Based on the analysis of the test results , the proportion of students' mistakes in solving math story that is 33 , 3 % misconception , 25 % fault Procedure 41.7 % technical error . From the percentage shown that a large proportion of most errors are technical errors. The percentage of the difficulties experienced by children with autism , a class V SDN mojo III Surabaya in doing math story problems is 33.3 % of students with autism have difficulty dyslexia, 33.3 % of students with autism have difficulty dysgraphia, and 33.3 % of students with autism have difficulty dyscalculia